2022
DOI: 10.1186/s13045-022-01252-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting extracellular matrix stiffness and mechanotransducers to improve cancer therapy

Abstract: Cancer microenvironment is critical for tumorigenesis and cancer progression. The extracellular matrix (ECM) interacts with tumor and stromal cells to promote cancer cells proliferation, migration, invasion, angiogenesis and immune evasion. Both ECM itself and ECM stiffening-induced mechanical stimuli may activate cell membrane receptors and mechanosensors such as integrin, Piezo1 and TRPV4, thereby modulating the malignant phenotype of tumor and stromal cells. A better understanding of how ECM stiffness regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
157
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(160 citation statements)
references
References 183 publications
3
157
0
Order By: Relevance
“…We also confirmed the inhibitory effect of OICR-9429 on the migration of Reh cells embedded in a 3D collagen matrix ( Movie S2 and Figures S5A-C ). The cell cytoskeleton acts as a mechanotransducer to integrate external 3D stimuli from the cell surface into the nucleus and might be a potential therapeutic target to improve cancer therapy, 18 therefore we addressed whether targeting WDR5 might affect the cytoskeleton of ALL cells. Flow cytometry showed that depletion or inhibition of WDR5 did not affect the level of F-actin in CCRF-CEM and Reh cells ( Figures 5D and S5D ).…”
Section: Resultsmentioning
confidence: 99%
“…We also confirmed the inhibitory effect of OICR-9429 on the migration of Reh cells embedded in a 3D collagen matrix ( Movie S2 and Figures S5A-C ). The cell cytoskeleton acts as a mechanotransducer to integrate external 3D stimuli from the cell surface into the nucleus and might be a potential therapeutic target to improve cancer therapy, 18 therefore we addressed whether targeting WDR5 might affect the cytoskeleton of ALL cells. Flow cytometry showed that depletion or inhibition of WDR5 did not affect the level of F-actin in CCRF-CEM and Reh cells ( Figures 5D and S5D ).…”
Section: Resultsmentioning
confidence: 99%
“…The tumor microenvironment (TME) represents the internal and external environment surrounding the tumor cells, which includes not only diverse functional cells but also some supportive noncellular components such as secreted signaling molecules and ECM ( Ho et al, 2020 ; Ganguly et al, 2022 ; Saw et al, 2022 ). As an essential component of TME, the ECM is known to be a dense network with structural proteins, bridging proteins, proteoglycans and enzymes that mainly provide biochemical and structural support for tumorigenesis and progression ( Ho et al, 2020 ; Gonzalez-Molina et al, 2022 ; Jiang et al, 2022 ). Various chemokines, inflammatory factors, cytokines and growth factors secreted from TME-associated inflammatory cells or stromal cells collectively constitute a dynamic microhabitat possessing diverse functional states through crosstalk with the ECM ( Wohlrab et al, 2014 ; Zhou et al, 2021 ).…”
Section: Nanotechnology Enhances Therapeutic Treatment For Neuroblastomamentioning
confidence: 99%
“…Disturbance of the PAM pathway is particularly usual in breast cancer, with approximately 70% of breast cancer patients having alterations in this pathway [ 18 , 19 ]. A huge number of experiments in vitro and in vivo have shown that inhibiting key components of the PAM pathway can inhibit cancer cell proliferation and survival, and affect tumor microenvironment, angiogenesis, cancer metastasis and metabolism, thereby exerting anti-tumor effects and overcoming endocrine therapy resistance [ 20 , 21 , 22 , 23 , 24 ]. Many of small-molecule inhibitors targeting the PAM pathway have been tested in preclinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%